An experimental study of the combined effects of n-hexane and methyl ethyl ketone. Issue 2 (May 1983) - Takeuchi, Y; Ono, Y; Hisanaga, N; Iwata, M; Aoyama, M; Kitoh, J; Sugiura, Y
Abstract : This study was intended to determine whether or not methyl ethyl ketone (MEK) enhances the neurotoxicity of n-hexane at low concentration and after long term exposure. Separate groups of eight rats were exposed to 100 ppm n-hexane, 200 ppm MEK, 100 ppm n-hexane plus 200 ppm MEK, or fresh air in an exposure chamber for 12 hours a day for 24 weeks. The body weight, motor nerve conduction velocity (MCV), distal motor latency (DL), and mixed nerve conduction velocities (MNCVs) were measured before exposure and after four, eight, 12, 16, 20, and 24 weeks' exposure. One rat of each group was histopathologically examined after 24 weeks' exposure. Exposure of 100 ppm n-hexane did not significantly decrease the functions of the peripheral nerve throughout the experiment. Exposure to 200 ppm MEK significantly increased MCV and MNCVs and decreased DL after four weeks' exposure, but at this later stage no significant changes were found throughout the experiment by comparison with the controls. Mixed exposure to 100 ppm n-hexane plus 200 ppm MEK significantly decreased by comparison with the controls. On histopathological examination of the tail nerve, however, no changes were found in any of the exposed groups or the controls. These results suggest that MEK might enhance the neurotoxicity of n-hexane at a low concentration, and mixed exposures to n-hexane and MEK should be avoided.